Primary and secondary esophageal contractions in patients with gastroesophageal reflux disease - Aben-Athar,C.G. (2006)
We studied the primary and secondary esophageal peristalsis in 36 patients with heartburn and acid regurgitation and in 14 asymptomatic volunteers. Primary peristalsis was elicited by ten swallows of a 5-mL bolus of water and secondary peristalsis was elicited by intra-esophageal infusion of 5, 10, and 15 mL water, 0.1 N hydrochloric acid and air. Esophageal contractions were measured by an 8-lumen manometric catheter assembly incorporating a 6-cm sleeve device. Contractions were registered at 3, 9, and 15 cm from the upper margin of the sleeve and the infusion was done through a side hole located at 12 cm. Twenty patients had normal endoscopic esophageal examination, 10 with normal (group I) and 10 with abnormal pH-metric examination (group II), and 16 had esophagitis (group III). The amplitude of contractions after swallows was lower (97.8 ± 10.0 mmHg) in the distal esophagus of group III patients than in controls (142.3 ± 14.0 mmHg). Patients of group III had fewer secondary contractions (water: 25% of infusion) than patients of the other groups and controls (67% of infusion). Patients of group III also had a lower amplitude of secondary peristalsis in the distal esophagus (water: 70.1 ± 9.6 mmHg) than controls (129.2 ± 18.2 mmHg). We conclude that patients with esophagitis have an impairment of primary and secondary peristalsis in the distal esophagus.